Book Review: Mitchell, M. (2009). Complexity: A guided tour - Steven K. Khan (Canadian Society for Studies in Education, 2010)
An expanded version of Melanie Mitchell's Ulam Memorial Lectures introduces new readers to some of the core historical and current sites of interest and samples of the biographical and cultural history of the sciences of complexity. Likely to become an important reference and supplement for those studying complexity theory in education.